Diseño de un caldero pirotubular a diésel para los pequeños productores de lácteos de la parroquia Pucayacu, del cantón La Maná provincia de Cotopaxi, año 2015 - Chunga Pazmiño, Cesar Ignacio (2016)
This concept refers to the design of a diesel fire tube boiler for small dairy farmers, for development of science and technology are essential tools as well as useful. An important resource in the process of determining proved engineering methods, these provided the facility to resolve and provide solutions to the problems experienced by dairy producers instantly process your raw material, which is of great importance to avoid the risk of massive contamination of the final product consumers elaborate. The proposed project aims to address this problem by performing the goals, starting with the design of the cauldron which should make the correct choice of type and model, analyze its benefits and limitations. Deploying the project engineering calculations developed, using tables could select materials and accessories, in addition to checking pressures and temperatures already established. Using simulated computer software to corroborate the results of the calculations, checking materials and accessories are suitable for the conditions of work required. Through a budget the cost of equipment compared to the same one of foreign origin was determined. To conclude some recommendations was raised and an operating procedure (Start and stop) was structured.